2018
DOI: 10.1002/jip.1502
|View full text |Cite
|
Sign up to set email alerts
|

Screening for intellectual disability in Dutch police suspects

Abstract: The screener for mild intellectual disability (SCIL) was developed to screen for mild intellectual disability (IQ below 85). The aims of this study were (a) to examine the predictive validity of the SCIL in screening for intellectual disability among police suspects and (b) to explore the prevalence of cognitive intellectual disability among suspects in police custody in the Netherlands. An unselected sample of police suspects (N = 178) charged with a variety of offences was assessed with the SCIL, aWechsler A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…In earlier validation studies, Cronbach’s alphas were found to have been 0.83 (adult sample) and 0.74 (youth sample; Nijman et al, ). Recently, the SCIL was also administered to a sample of 178 suspects who were placed into police custody awaiting interrogation (Geijsen, Kop, & De Ruiter, ). In this sample, Cronbach’s alpha was 0.64, whereas the AUC value for predicting the outcomes of a brief version of the WAIS was 0.78.…”
Section: Discussionmentioning
confidence: 99%
“…In earlier validation studies, Cronbach’s alphas were found to have been 0.83 (adult sample) and 0.74 (youth sample; Nijman et al, ). Recently, the SCIL was also administered to a sample of 178 suspects who were placed into police custody awaiting interrogation (Geijsen, Kop, & De Ruiter, ). In this sample, Cronbach’s alpha was 0.64, whereas the AUC value for predicting the outcomes of a brief version of the WAIS was 0.78.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies, published by independent researchers, have cited the research underpinning and/or used the LDSQ and CAIDS-Q as part of their own research. This has included their potential use by nurses (Delahunty, 2017); in homeless services (Stone et al, 2019); in relation to the impact of immigration on mental health (von Werthern et al, 2018); in criminal justice services (Ali and Galloway, 2016;Board, Ali and Bartlett, 2015;Boer et al, 2016;Chaplin et al, 2017;Courtney and Lascelles, 2010;Ellem and Richards, 2018;Forrester et al, 2017;Geijsen, Kop and de Ruiter 2018;Gudjonsson, Gonzalez and Young 2019;Gulati et al, , 2018aKaal, 2010;Kaal, Nijman and Moonen 2015: McCarthy et al, 2015McKinnon, Thorp and Grube, 2015;Murphy, Gardner and Freeman 2015;O'Mahony, Smith and Milne, 2011;Poynter, 2011;Sarrett, 2017;Sen et al, 2018;Short et al, 2018;Silva, Gough and Weeks 2015;Wakeling and Ramsay, 2019;Young et al, 2013Young et al, , 2018; as part of treatment and intervention studies (Idro et al, 2019;Hall et al, 2019); as part of the neuropsychological assessment or screening processes (Aubry and Bourdin, 2018;Bjørgen, Gimse and Søndenaa. 2016;Doyle and Mattson, 2015;McInnis, Hills and Chapman 2012;Murphy, 2019;…”
Section: Research or Methods Used By Other Researchers In Subsequent ...mentioning
confidence: 99%
“…Its 14 items include educational background, preferred journals or magazines, availability of social support and arithmetic (calculation), reading and writing (spelling exercise), language comprehension and behaviour tasks. Psychometric data for the SCIL are from four studies, one each in correctional, forensic, community (Nijman et al , 2018; Nieuwenhuis et al , 2017; Kaal et al , 2015) and police custody settings (Geijsen et al , 2018). Discriminant validity appears strong and justifies further investigation.…”
Section: Resultsmentioning
confidence: 99%